Focal Adhesion Kinase and β‐Catenin Cooperate to Induce Hepatocellular Carcinoma. Issue 5 (22nd June 2019) - Shang, Na; Wang, Hao; Bank, Thomas; Perera, Aldeb; Joyce, Cara; Kuffel, Gina; Zilliox, Michael J.; Cotler, Scott J.; Ding, Xianzhong; Dhanarajan, Asha; Breslin, Peter; Qiu, Wei
Abstract : There is an urgent need to understand the molecular signaling pathways that drive or mediate the development of hepatocellular carcinoma (HCC). The focal adhesion kinase (FAK) gene protein tyrosine kinase 2 is amplified in 16.4% of The Cancer Genome Atlas HCC specimens, and its amplification leads to increased FAK mRNA expression. It is not known whether the overexpression of FAK alone is sufficient to induce HCC or whether it must cooperate in some ways with other oncogenes. In this study, we found that 34.8% of human HCC samples with FAK amplification also show β‐catenin mutations, suggesting a co‐occurrence of FAK overexpression and β‐catenin mutations in HCC. We overexpressed FAK alone, constitutively active forms of β‐catenin ( CAT ) alone, or a combination of FAK and CAT in the livers of C57/BL6 mice. We found that overexpression of both FAK and CAT, but neither FAK nor CAT alone, in mouse livers was sufficient to lead to tumorigenesis. We further demonstrated that FAK's kinase activity is required for FAK/CAT‐induced tumorigenesis. Furthermore, we performed RNA‐sequencing analysis to identify the genes/signaling pathways regulated by FAK, CAT, or FAK/CAT. We found that FAK overexpression dramatically enhances binding of β‐catenin to the promoter of androgen receptor (AR), which leads to increased expression of AR in mouse livers. Moreover, ASC‐J9, an AR degradation enhancer, suppressed FAK/CAT‐induced HCC formation. Conclusion: FAK overexpression and β‐catenin mutations often co‐occur in human HCC tissues. Co‐overexpression of FAK and CAT leads to HCC formation in mice through increased expression of AR; this mouse model may be useful for further studies of the molecular mechanisms in the pathogenesis of HCC and could lead to the identification of therapeutic targets.